Intermittent fasting improves metabolic outcomes in metabolic syndrome: a systematic review and meta-analysis with GRADE evaluation - Song, Qian; Almutairi, Alaa Sultan H.; Almutairi, Manal Fehaid A.; Jamilian, Parmida; Abu-Zaid, Ahmed (Frontiers in Nutrition, 2025)
BackgroundPrevious studies have demonstrated that intermittent fasting (IF) has garnered scientific attention and gained recognition for its beneficial effects on metabolic outcomes. However, the results are inconsistent. Accordingly, this systematic review and meta-analysis aimed to evaluate the effect of fasting on glycemic control, lipid profile, and inflammatory markers.MethodsDatabases such as PubMed, Embase, Cochrane, Scopus, and Web of Science were used to retrieve relevant studies published until September 2025. The quality of the included studies was evaluated using the Cochrane Risk-of-Bias 2 (RoB2) tool. Moreover, the Grades of Recommendation, Assessment, Development, and Evaluation (GRADE) approach was employed to evaluate the quality of evidence.ResultsA total of 10 studies, involving 701 individuals, were included in the current meta-analysis. The combined effect of various types of fasting significantly reduced fasting blood sugar (FBS) [standard mean difference (SMD) = −0.51; 95% confidence interval (CI): −0.81, −0.20; p = 0.001], insulin (SMD = −0.27; 95% CI: −0.52, −0.03; p = 0.027) and Homeostatic Model Assessment for Insulin Resistance (HOMA-IR) (SMD = −0.39; 95% CI: −0.65, −0.12; p = 0.004), and HbA1c (SMD = −0.25; 95% CI: −0.49, −0.02; p = 0.034) levels. Moreover, the regimen successfully exerted its beneficial effect on low-density lipoprotein cholesterol (LDL-C) (SMD = −0.34; 95% CI: −0.53, −0.14; p = 0.001) and interleukin-6 (IL-6) (SMD = −0.30; 95% CI: −0.57, −0.03; p = 0.029) levels as well. The sensitivity analysis indicated that excluding any single study had no effect on the overall effect size (ES) for FBS, blood sugar (BS), HOMA-IR, LDL-C, and high-density lipoprotein cholesterol (HDL-C). Moreover, the results of the GRADE approach scored high quality of evidence for FBS, insulin, HOMA-IR, HbA1c, total cholesterol (TC), LDL-C, and IL-6, which suggests the robustness of the results. No evidence of publication bias was detected using Egger’s and Begg’s test (p > 0.05).ConclusionThe findings suggest that intermittent fasting may have favorable effects on the metabolic panel, specifically, FBS, insulin, HOMA-IR, (HbA1c), LDL-C, and IL-6 levels.